KAJIAN HUKUM TERHADAP PENGGUNAAN HANDPHONE OLEH DRIVER OJEK ONLINE PADA SAAT BERKENDARA - Anton Hermawan (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT GOJEK is a company engaged in the field of online transportation that is managed by PT GOJEK INDONESIA, in carrying out its work online motorcycle taxi drivers often use mobile phones in driving, this is inseparable because of their work related systems that require viewing mobile phones to view orders, orders, and view GPS to arrive at this destination can disrupt concentration in driving and can endanger other motorists.This type of research used in this study is a type of normative legal research, which is a legal research method that uses a statutory approach.The results showed that the use of mobile phones while driving was not permitted because it could interfere with concentration and could endanger other motorists, this has been explained by law number 22 of 2009 concerning road traffic and transportation, and was also confirmed by the constitutional court number 23 / PUU-XVI / 2018 that the use of mobile phones while driving is not permitted because it can cause accidents. Keywords: Legal Study, Mobile Usage, Online Ojek Drivers.